A technological review of dew point evaporative cooling: experimental, analytical, numerical and optimization perspectives - Alam, Md Shadab; Zubir, Mohd Nashrul Bin Mohd; Bin Muhamad, Mohd Ridha; Kazi, Salim Newaz; Öztop, Hakan Fehmi; Abdullah, Shekh; Shaikh, Kaleemullah (Elsevier, 2024)
Based on the Maisotensko cycle (M-cycle), dew point evaporative cooling (DPEC) technology is a promising solution to address the growing demand for affordable and sustainable cooling in buildings. This review article thoroughly explores the experimental, theoretical, and optimization methodologies used to assess the effectiveness of a dew point evaporative cooling system. The main findings indicate that innovations in the design and structure of heat and mass exchangers (HMX), advancements in wet materials, and improvements in water distribution systems can significantly enhance DPEC performance by maximizing heat transfer between dry and wet channels. Analytical solutions, numerical simulations, and statistical design methodologies have been employed to evaluate DPEC system characteristics, facilitating a comprehensive understanding and comparison. It was found that computational fluid dynamics (CFD) tools considering heat and mass transport from porous materials improve the design parameters. The genetic algorithm based multi-to-single objective optimization (MSOO) technique will enhance the performance significantly. Practical implications include integrating DPEC with liquid desiccant and vapor compression refrigeration (VCR) systems, demonstrating high energy-saving potential. In conclusion, combining DPEC technology with energy-efficient building design, including intelligent heating, ventilation, and air conditioning (HVAC) systems, with advanced materials such as aerogel, metal-organic frameworks (MOFs), and phase change materials (PCMs) coupled with artificial intelligence (AI), offers a promising solution towards achieving sustainability goals and achieving zero carbon footprint.
Keywords: Dew point evaporative cooling; Heat and mass exchanger; Analytical model; Numerical simulation; Optimization